Second language learning role-play: effects of patient and doctor roles on motivation and competence - Yu, Hao; Isahakyan, Anna; van Merrienboer, Jeroen J. G.; Köhler, S. Eleonore; Asoodar, Maryam (Frontiers in Medicine, 2023)
Objectives Role-playing has motivated foreign language learners for decades. In doctor–patient medical consultation role-plays, the doctor role has always been considered an important learning opportunity, whilst the patient role remained obscured. Our study, therefore, had a dual focus. We first explored how intrinsic motivation changes medical second-language (L2) learning through the lens of self-determination theory. We subsequently examined if playing the role of the patient provides additional value to medical L2 learning. Methods We performed a mixed-methods study using a one-group pretest–posttest design. Participants were 15 student volunteers learning medical Dutch through peer role-play in medical consultations. Students completed a questionnaire before and after the course that measured changes in their intrinsic motivation to experience stimulation (IMES), feeling of relatedness, and feeling of competence. We also measured students' competence through a peer-rated checklist and the final course grades. At the end of the course, the students participated in semi-structured interviews to discuss their experience acting as patients. The data were subjected to the Wilcoxon signed-rank test and a thematic analysis. Results The pre- and post-questionnaires revealed that students' IMES as well as their feeling of relatedness increased. Their self-perceptions, feeling of competence, peer assessments, and final course grades demonstrated that students were competent in medical L2. Our thematic analysis led to the identification of five themes of the role-play exercise for medical L2 learning: (1) motivational experience, (2) supportive peer interaction, (3) setting up a role-play environment for medical L2 learning, (4) utilizing the patient role to benefit medical L2 learning, and (5) a novel patient perspective on the doctor's role. Discussion Our study found that role-play, by enhancing students' intrinsic motivation, feeling of relatedness, and competence development, aids the medical L2 learning process. Interestingly, playing a patient role in medical consultation was also found to support this process. We welcome future controlled experiments to confirm the positive impact of playing the role of the patient in medical consultation.